LEARNING AND IMPROVING ENGLISH SKILL WITH PHONETIC SYMBOL - Nazwa Kaila; Indah Alya Isnani; Yani Lubis (CENDEKIA INDONESIA, 2024)
Phonetic symbols are a fundamental aspect of linguistics, enabling the representation and study of sounds across languages.Effective communication relies heavily on pronunciation, which helps language learners express their ideas and thoughts intelligibly. But learning the subtleties of pronunciation can be difficult. The good news is that phonetic symbols offer a useful tool to support students as they work toward precise pronunciation. Language learners can accurately transcription and categorize speech sounds by using phonetic symbols. These symbols bridge the gap between spoken words and written symbols by providing a visual representation of sounds. The International Phonetic Alphabet (IPA) is one standardized set of symbols that linguists use to accurately represent the articulatory and auditory characteristics of sounds.This research will explore of phonetic symbols and offer guidance on how students can use them to enhance their pronunciation abilities.